Analisis framing pemberitaan ijazah palsu Jokowi di CNN Indonesia dan Republika (periode April-Mei 2025) - Ahmad Arya Subarkah; Heidy Arviani (Universitas Garut, 2026)
Abstract This study was driven by the widespread coverage of the alleged fake diploma issue involving Jokowi in online media during the period of April–May 2025. During this period, there were two important moments, namely the filing of the first civil lawsuit at the Solo District Court and the announcement of the forensic test results by Bareskrim Polri. As mainstream media, CNN Indonesia and Republika have different ideological orientations and editorial styles, which affect how both construct and narrate the alleged fake diploma issue involving Joko Widodo to the public. CNN Indonesia is generally known for emphasizing unbiased presentation of data, concise language, and a thematic narrative style, whereas Republika places greater emphasis on moral dimensions and social conflict in its reporting. The purpose of this study is to analyze the differences in framing of the alleged fake diploma coverage of Jokowi in the two media outlets. This study uses a descriptive qualitative approach with Robert M. Entman’s framing analysis model. The unit of analysis consists of eight news articles, four from CNN Indonesia and four from Republika, selected through digital archive searches on the websites of the two media outlets using the keyword “Jokowi fake diploma.” The findings show that CNN Indonesia tends to frame the issue in a procedural and verificative manner by highlighting institutional authority, legal certainty, and the results of the official investigation as a way to close the controversy. Meanwhile, Republika places greater emphasis on actor conflict, demands for public transparency, and the moral and political dimensions of the Jokowi diploma issue. This study is expected to contribute academically to the development of online media framing studies, as well as serve as a reference for journalism practitioners in presenting news in a more balanced, objective, and high-quality manner. Keywords: Framing; Robert M. Entman; Jokowi’s Fake Diploma; CNN Indonesia; republika. Abstrak Penelitian ini dilatarbelakangi oleh maraknya pemberitaan mengenai dugaan ijazah palsu Jokowi di media daring pada periode April–Mei 2025. Terdapat dua momen penting pada periode tersebut, yaitu pengajuan gugatan perdata pertama di Pengadilan Negeri Solo serta pengumuman hasil uji forensik oleh Bareskrim Polri. Sebagai media arus utama, CNN Indonesia dan Republika memiliki orientasi ideologis serta gaya editorial yang berbeda, sehingga memengaruhi cara keduanya mengonstruksi dan menarasikan isu dugaan ijazah palsu Joko Widodo kepada khalayak. CNN Indonesia cenderung dikenal mengedepankan penyajian data tanpa bias, bahasa yang padat, dan gaya narasi yang tematik, sedangkan Republika lebih menonjolkan dimensi moral serta konflik sosial dalam pemberitaannya. Tujuan kajian ini untuk menganalisis perbedaan framing pemberitaan dugaan ijazah palsu Jokowi pada kedua media tersebut. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode analisis framing model Robert M. Entman. Unit analisis terdiri dari delapan berita, masing-masing empat berita dari CNN Indonesia dan Republika, yang dipilih melalui penelusuran arsip digital pada website kedua media dengan kata kunci “ijazah palsu Jokowi. Hasil penelitian menunjukkan bahwa CNN Indonesia cenderung membingkai isu secara prosedural dan verifikatif dengan menonjolkan otoritas institusional, kepastian hukum, dan hasil penyelidikan resmi sebagai penutup polemik. Sementara itu, Republika lebih menonjolkan konflik aktor, tuntutan transparansi publik, serta dimensi moral dan politis dari isu ijazah Jokowi. Penelitian ini diharapkan dapat menjadi kontribusi akademik dalam pengembangan kajian framing media daring, serta menjadi referensi bagi para pelaku industri jurnalistik dalam menyajikan berita secara lebih berimbang, objektif, dan berkualitas. Kata-kata kunci: Framing; Robert M. Entman; Ijazah Palsu Jokowi; CNN Indonesia; republika.